2013
DOI: 10.1144/geochem2012-137
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical assessment of arsenic toxicity in mine site along the proposed Mineral Tramway Project, Camborne, Cornwall

Abstract: Many abandoned mine sites in Cornwall, UK, are characterised by elevated concentrations of arsenic which can cause contamination of surrounding soil and water resources. Often these sites have important historical and cultural value that requires access to be maintained, despite the potential toxicity of As. In west Cornwall, the potential for As contamination has been recognized within the Industrial World Heritage site focused on the Mineral Tramway and mining sites mines in the Gwennap and Camborne mining d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
1
9
1
Order By: Relevance
“…We note that another facility in the Cornwall and West Devon Mining Landscape UNESCO World Heritage Site (a series of interconnecting mineral tramways 70 km to the west of DGC) that was opened to the public was subject to retrospective remediation measures, including restricting access to certain areas, removal of waste and covering tailings with top soil. This followed reports of As concentrations and bioaccessibilities in soils, tailings and overburden at targeted sites along the converted trails that were elevated (but whose median values were an order of magnitude lower than those reported here; 1770 g g -1 , n = 38) (Bowell et al, 2013).…”
Section: Discussionmentioning
confidence: 73%
“…We note that another facility in the Cornwall and West Devon Mining Landscape UNESCO World Heritage Site (a series of interconnecting mineral tramways 70 km to the west of DGC) that was opened to the public was subject to retrospective remediation measures, including restricting access to certain areas, removal of waste and covering tailings with top soil. This followed reports of As concentrations and bioaccessibilities in soils, tailings and overburden at targeted sites along the converted trails that were elevated (but whose median values were an order of magnitude lower than those reported here; 1770 g g -1 , n = 38) (Bowell et al, 2013).…”
Section: Discussionmentioning
confidence: 73%
“…Arsenic may form toxic dust that can rest on garden soils and footpaths that young children may ingest via hand to mouth (Bowell, et al, 2013). Arsenic is a known toxin (Pascoe et al, 1994 ;Lorenzana et al, 1996;Farago et al, 1997;Kenyon et al, 2008;Pinyayev et al, 2011) and numerous studies have demonstrated higher As uptake in children (Eligali, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Towards the end of the nineteenth century, Cornwall dominated copper, tin and arsenic production globally (Buckley, 2005). Prolonged periods of mining without environmental regulations have had a significant impact to the surroundings (Farago et al, 1997;Camm et al, 2004;Bowell et al, 2013). One such mine, the Wheal Maid is located in the Poldice Valley in central Cornwall (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…historical management of mine waste or drainage (Lottermoser, 2003;Rytuba, 2005;Frau et al, 2009;González et al, 2012;Bowell et al, 2013). This can result in contamination of surrounding soil and water resources and may have associated ecological and human health impacts.…”
mentioning
confidence: 99%
“…A nine-step selective extraction procedure was undertaken by ACZ laboratories, Colorado, on seven surface soil samples collected from mill sites to determine the partitioning and chemical nature of arsenic, mercury and lead within the Comstock district based on the scheme presented by Bowell et al (2013). The method targets soluble salts and adsorbed ions in addition to amorphous and crystalline phases using the extraction steps described in Table 1.…”
mentioning
confidence: 99%